THE ROLE OF ACUPUNCTURE IN A SYSTEMIC LUPUS ERYTHEMATOSUS PATIENT: A CASE STUDY - Mayang Wulandari; Amal Prihatono (Journal of Vocational Health Studies, 2026)
Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease commonly characterized by symptoms such as frequent headaches, joint pain, and occasional body swelling. Acupuncture, a traditional Chinese medicine therapy, has been identified as a possible alternative for managing symptoms in SLE patients, especially for those seeking relief from the side effects of conventional treatments. Purpose: This study aims to evaluate the effectiveness and safety of acupuncture, a minimally invasive therapy, in addressing chronic and complex complaints in a SLE patient. Case analysis: A case study was conducted on a 23-year-old woman diagnosed with SLE presenting complaints of frequent headaches, joint pain, and occasional body swelling. Data were collected through observation, hearing (auscultation)/smelling (olfaction) assessment, interview, and palpation. The patient underwent 12 acupuncture sessions with assessments conducted before and after therapy, including Traditional Chinese Medicine (TCM) examination, abdominal ultrasound, chest X-ray, and laboratory tests. Result: Following acupuncture therapy, the patient’s headaches were resolved, joint pain diminished, and swelling subsided. Conclusion: Acupuncture can be an effective supportive therapy and a safe option for reducing various symptoms in SLE patients.